Q: 5 plus 7 ac plus 3b plus 3ac?

Write your answer...

Submit

Related questions

5b plus 5-3b-7 is 2b-2.

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

5+3b? :3

a+b+2+3=5+a+b

It is: 19a+27b-9 simplified

3b-8b = -5

8a-3b = 5

(11, 5)

3b -1

It is an expression that can be simplified to: 1-4b-5c

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab

if you meant to write the problem as "3b + 5 = 29", then this is how to solve: 3b + 5 = 29 - 5 - 5 subtract 5 from each side 3b = 24 simplify b = 8 divide each side by 3 to get b by itself

a = 11 and b = 5.

-13

2a-3+4b-2a-b-3+5=3b-1

b + b + b + 7 = 223b + 7 = 223b = 15b = 5

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

3b2 + b - 10 = 0 This quadratic equation can be factored. (3b -5)(b +2) = 0 The equation can be solved when either (3b - 5) = 0, or (b + 2) = 0. If 3b - 5 = 0 then 3b = 5 : b = 5/3 If b + 2 = 0 then b = -2 The roots or solutions to this equation are b = 5/3 and b = -2

50 - 3b = 353b = 50 - 353b = 15b = 5

The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3

5

It is a linear equation in two unknown variables, a and b. It can be simplified (slightly) but cannot be solved becasue to solve with two unknowns you need two independent equations. Incidentally, a + 5 = (a - 7) + 12 = (3b + 2) +12 = 3b +14

-2

4(3b - 5) < -31 + 12b12b - 20 < -31 + 12b, this is not true because -20 > - 31, so that the solution for the given inequality does not exist.

Study guides